Produção e Caracterização Bioquímica do complexo amilolítico de Humicola brevis var. thermoidea e sua aplicação na sacarificação do amido - Camila Langer Marciano (2023)
Among the enzymes used in bioprocesses, amylases represent a versatile group of biocatalysts used by industry in starch saccharification. This is because they are enzymes capable of hydrolyzing the glycosidic bonds of starch and releasing glucose, maltose, and short chains of oligosaccharides and therefore represent 30% of the global enzyme market. Among amylase producers, thermophilic filamentous fungi are promising microorganisms for biotechnology applications, as they can hydrolyze agricultural by-products and generate high-value-added products through the solid-state fermentation technique (SSF). Because of this, the amylolytic complex of the thermophilic filamentous fungus Humicola brevis var. Thermoidea (AmyHb), comparing it with the commercial amylase Termamyl®, as well as investigating its biotechnological application in starch saccharification. Thus, enzyme production was optimized in FES, which showed the highest production in a medium containing wheat bran at 50°C for 5-6 days, without the addition of inducers. The optimal amylolytic activity occurred at pH 5.0, at 60°C and remained stable between pH 5.0 to 6.0, with thermostability at 50°C and 60°C, mainly in the presence of Ca2+, better results than found by Termamyl®. Both enzymes were strongly inhibited by Hg+2, Cu+2, and Ag+, however, AmyHb increased activity in the presence of Mn+2 and Na+. In addition, AmyHb was not inhibited in the presence of organic solvents and showed greater tolerance in a wide range of NaCl and ethanol, having a better performance in hydrolyzing potato starch and maltose when compared to commercial amylase. Analysis of the electrophoresis gel showed that AmyHb has a molecular mass close to 48 and 43kDa. The cornstarch flour hydrolysis assays demonstrated that the Cocktail (AmyHb50%+Termamyl®50%) significantly increased the release of glucose and total reducing sugars when compared to the enzymes alone. The partial purification of AmyHb, together with the characteristics observed by the experiments, suggest that H. brevis produces two different amylases, but with very similar molecular weights, which makes their separation and purification difficult. Thus, the amylolytic complex of H. brevis presents promising physicochemical properties, with a good performance associated with commercial amylase, which proves to be a promising biotechnological alternative for application in the bioprocessing of amylaceous sources.